(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Language – complex, versatile and multifaceted and multidimensional quantity that is in constant motion. One of its features is the natural modification of linguistic units (the phenomenon of variance). The article discusses and analyzes the views of Ukrainian and foreign linguists to the problem of variation of the words. The prospects for further research investigated linguistic phenomenon.